Advances and Opportunities in the Study of Political Communication, Foreign Policy, and Public Opinion. (2nd October 2017) - Rothschild, Jacob E.; Shafranek, Richard M.
Abstract : We review contemporary research at the intersection of political communication and foreign policy, highlighting four themes: 1) new, more realistic and psychologically-nuanced approaches that account for limited information and issue framing; 2) the question of whether the flow of communication between the state and the public is best conceived as a closed system, or one that is open to outside influences such as foreign elites; 3) how variations in political or governmental structures, patterns of media access or ownership, and other institutional factors can alter the relationships between foreign policy and communication processes; and 4) whether or not it is useful to distinguish between foreign and domestic policymaking when analyzing the role of political communication. We also suggest avenues for further research in each section and conclude by summarizing these opportunities for continued theoretical development.